Fundamen tals for the po sitiv e dev elo pm ent ofth e ch ild - Royo García, Pilar; Prado Novoa, Carmen; Maíllo Urones, Inmaculada (Pulso. Revista de educación, 2012)
This article stems from our interest to incorporate the contributions that are being carried out from Positive Psychology and Positive Education in the subjects related to the field of Psychology included in our Teacher Training and Social Education University degrees. Throughout the text the authors justify, first, the importance of incorporating these contributions to these subjects; second, the variables which favor the optimization of children and youth development, based on proposals made by some international institutions. Finally, since it would be impossible to reflect on all the variables presented, two of them are thoroughly described, i.e., the need to establish safe and trusting social bonds with the learner, and the need to provide them with situations which make them have a successful experience, with the aim of highlighting the importance of teachers/educators have them present in their everyday practice.
Keywords: Positive Development; Positive Education; Reference Adult; Attachment; Opportunities of Success